Dabrafenib and its use in the treatment of metastatic melanoma. (August 2015) - Bowyer, Samantha; Lee, Rebecca; Fusi, Alberto; Lorigan, Paul
Approximately 50% of melanomas have mutations in the gene encoding BRAF . In recent years, new targeted therapies have transformed the landscape of metastatic melanoma treatment. Dabrafenib, a potent kinase inhibitor of mutated BRAF, has been showed to have high response rates with a rapid onset of response, as well as improved overall and progression-free survival when compared with chemotherapy. Dabrafenib in combination with trametinib, a MEK inhibitor, has demonstrated higher responses and improved clinical efficacy compared with monotherapy. Toxicity is distinct compared with chemotherapy but manageable. This article summarizes the pharmacology, key clinical trial data as well as practical experience with dabrafenib in clinical practice, and future directions.